Can you please show the line plot or send a picture through my profile. I may be able to help you then.
Answer:
D(1, 2) → D'(2, 7)
E(-3, -5) → E'(-10, 0)
F(4, -1) → F'(11, 4)
Step-by-step explanation:
D(1, 2) → D' ________
Translate image (3x - 1, y + 5)
(1, 2), x = 1 and y = 2
3x - 1 = 3(1) - 1 = 3 - 1 = 2
y + 5 = (2) + 5 = 7
E(-3, -5) → E' ________
(-3, -5), x = -3 and y = -5
3x - 1 = 3(-3) - 1 = -9 - 1 = -10
y + 5 = (-5) + 5 = 0
F(4, -1) → F' ________
(4, -1), x = 4 and y = -1
3x - 1 = 3(4) - 1 = 12 - 1 = 11
y + 5 = (-1) + 5 = 4
Answer: C. 7x/6
Step-by-step explanation: Simplify the expression.
Hope this helps you out! ☺
Answer:
1) vertical-Line test
2)y=x
3)x
4)domain
Step-by-step explanation: